Jews, Gentiles, and “in Christ” Identity: A Post-Supersessionist Reading of Philippians - Christopher Zoccali (Religions, 2023)
Interpretations of Philippians have commonly suggested that the letter seeks to demonstrate the worthlessness of Paul’s own (former) Jewish identity, and thus that the Philippians should not be led astray by those who would persuade them to adopt the Jewish Law. Accordingly, it is assumed that Paul understands Judaism to have been superseded by Christianity and, moreover, that Christian identity has superseded all other identities that persons may have possessed upon entrance into the Christ community. In contrast to this long-standing interpretive tradition, this article contends that, for Paul, the ethnic distinction between Jew and gentile within the greater Christ community remains intact, along with a continued role for the Torah for both subgroups. Rather than advancing a supersessionist agenda, Paul fundamentally seeks in this letter to strengthen the Philippians’ identity as members of the nations who have, alongside those in Israel, become members of God’s holy, multiethnic people.